Psychosocial Factors of Stock Investors’ Inclination: The Case of the South Pacific Stock Market - Saliya, Candauda Arachchige Arachchige (Universitas Islam Indonesia, 2023)
Previous research has documented that psychosocial resources and socioeconomic status have significant influences on investment behavior in financial assets. There are currently no studies available about the motivating factors of individual investor participation in the South Pacific Stock Market to the researcher’s knowledge. This study investigates the motivating factors of existing and potential stock market investors in countries with similar socio-cultural backgrounds. Using a purposive sample of potential stock investors in Fiji, the study sample included 162 participants with university education (banking and finance). Two research assistants were involved in collecting data, and 108 questionnaires were received via email and Google forms while the balance 54 were collected physically.The researcher tested how enterprising personality plays a mediating role in relation to the association between individual characteristics and investment behavior in the Structural Equation Modeling (SEM) framework. The results revealed that four latent factors (intuition, education and knowledge, sociocultural norms, and enterprising personality) are distinct dimensions of investment inclination together with the maturity factor (age) towards stock investments. The findings will be useful for financial service providers and regulators in designing educational programs to enhance enterprising personality qualities amongst people generally, and inculcate positive attitudes towards stock investments in the young through high school curricula and mass-awareness programs.